1978
DOI: 10.1002/tera.1420180211
|View full text |Cite
|
Sign up to set email alerts
|

Cell ploidy in molar placental disease

Abstract: Molar diseases of the placenta is associated with cystic change in the villi. The cysts may be from 5-20+ mm in diameter. This disease has been described in association with triploid and diploid cell lines and with and without an accompanying embryo or fetus. It may be followed by malignant change and invasive chorio-carcinoma. In order to investigate the association between cell ploidy, embryonic development and subsequent malignancy, a detailed study of 30 conceptuses with molar disease was made, with the ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1980
1980
1990
1990

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…In attempting to define a phenotype for triploid fetuses, Harris et al (1981) suggested that the diagnosis should be suspected when cystic placental changes are found to be associated with fetal malformations. Under such circumstances, cytofluorometric DNA measurements on fetal blood samples or placental tissue could be extremely helpful in demonstrating the presence of triploid cellular DNA content (Harris et al, 198 1;Poland and Baillie, 1978;Kunze, 1978). We were able to document the usefulness of this technique for three of the cases described herein.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…In attempting to define a phenotype for triploid fetuses, Harris et al (1981) suggested that the diagnosis should be suspected when cystic placental changes are found to be associated with fetal malformations. Under such circumstances, cytofluorometric DNA measurements on fetal blood samples or placental tissue could be extremely helpful in demonstrating the presence of triploid cellular DNA content (Harris et al, 198 1;Poland and Baillie, 1978;Kunze, 1978). We were able to document the usefulness of this technique for three of the cases described herein.…”
Section: Discussionmentioning
confidence: 59%
“…Triploidy occurs frequently among early spontaneous abortions, comprising 20 per cent of all chromosomally abnormal fetuses (Boue et al, 1975;Carr and Gideon, 1978). Triploidy is often associated with molar changes of the placenta (Szulman and Surti, 1978a, b;Szulman et al, 1981a, b;Poland and Baillie, 1978). In fact, Ornoy et al (1978) suggested that the association of triploidy with molar placental changes may be one of the major reasons for loss of triploid pregnancies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…, in those in whom inactivation of an X-chromosome occurred. A partial hydatidiform molar placenta is present in 85% of triploidies; all partial moles may be considered triploidies until proven otherwise [398][399][400] .…”
Section: Triploidymentioning
confidence: 99%
“…Interestingly, triploid cell lines are always associated with an embryo or fetus where cystic disease of the villi has been found, and triploidy is not associated with hyperplastic changes in the trophoblast. 26 In a study of spontaneous human abortuses with normal and abnormal karyotypes, Honor6 et al27 were able to correlate placental morphology and the karyotype of the conceptus. Heteroploid abortuses could be differentiated from the diploid.…”
Section: Cardiovascular Systemmentioning
confidence: 99%